Estimativa de vida residual de rotores de turbinas a vapor expostos aos mecanismos de dano por fluência e fadiga - Cardoso, Bruno Reis (2017)
Thermal power plants represent approximately 25% of Brazil’s energy matrix and operate, most of the times, in cyclic regime, in order to supply seasonal demand peaks. This operational behavior may lead in a series of non predicted damages and losses, because most of the plants are designed to operate in base load, with the least number of start/stop cycles as possible. The development of a methodology that may estimate remaining life and accumulated damage, taking in consideration materials properties appropriately, that could be less conservative and that could use operational records seems to be interesting to enrich integrity evaluations and to provide a faster answer to operation and maintenance engineers. The objective of the present study is the development of a methodology to calculate the accumulated damage and the consumed life of components that are subjected to creep and fatigue damage mechanisms. The high pressure rotor of a steam turbine was evaluated, due to the severe conditions related to high temperatures and pressures. The proposed methodology once combined with a computational system presented itself as a powerful tool for the evaluation of the operational condition of rotors and may be used by the operation and maintenance teams in the decision making process of stopping or running the units.